Dinamika Multikulturalisme Muslim di Australia - Ningrum, Velida Apria; Ulya, Nur Afina (IAIN Syekh Nurjati Cirebon, 2024)
This article investigates the process of Islamization and development in Australia amid multiculturalism. The process of Islamization began in the 17th century, when Makassar fishermen looking for seagulls came. When Muslim immigrants arrived from Egypt, Saudi Arabia, China, Jordan, Syria, Malaysia, and Indonesia, Islamization became more visible. Throughout its history, Islam has always battled minority rights and terrorism challenges. The presence of various Islamic groups in Australia, including the Australia Federation of Islamic Councils (AFIC), the Australian Federation for Muslim Students and Youth (FAMSY), and the Muslim Women's Center (MWA), signaled the expansion of Islamization in the country. The study employs qualitative methodologies in conjunction with a literary review strategy. Primary data sources are consulted.